Pengaruh Pemberian Ensim Amilase terhadap Kadar Bioetanol dari Limbah Sagu Padat - Muhammad Lukman Hakim; Endah Dwi Hastuti; Sarjana Parman (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Sago starch processing industry in the village Plajan leaving solid waste that pollute the environment. Solid sago waste still contains carbohydrates ± 84.7%, which can be used as a base material for bioethanol production. Giving amylase enzyme in this study aims to optimize the starch hydrolysis process into glucose so as to increase the levels of bioethanol. The purpose of this study was to determine the effect of amylase enzyme with different volumes on levels of bioethanol. The research methods include hydrolysis, fermentation and distillation. The study design used was completely randomized design (CRD) with four treatments. Such treatment is A = 0 ml of α-amylase and glucoamylase 0 ml (control), B = 2 ml α-amylase and 2 ml of glucoamylase, C = 4 ml of α-amylase and glucoamylase 4 ml, D =6 ml of α-amylase and 6 ml glucoamylase three replications. Parameters observed that glucose levels, levels of ethanol, and the volume of bioethanol. Analysis of the data by Analysist Variance (ANOVA), followed by Duncan's Multiple Test Test (DMRT). These results indicate that administration of amylase enzyme is able to increase levels of ethanol until a certain volume. The most effective enzyme volume to produce the highest levels of bioethanol is the range of volume 2 ml α-amylase and 2 ml glucoamylase to 4 ml of α- amylase and 4 ml glucoamylase of ethanol grading 63.33% to 69.00% with a distillation process the distillation temperature between 70-90oC.Keywords: Amylase, bioethanol, sago solid waste.